2019
DOI: 10.1002/cncr.32523
|View full text |Cite
|
Sign up to set email alerts
|

Improving access to cancer clinical trials by reducing the financial burden

Abstract: Cancer clinical trials are vital to improving cancer care, but participation may add an additional financial burden for individuals and families already struggling to bear the high cost of cancer care. Finding sustainable ways to reduce financial toxicity, particularly for low‐ and middle‐income patients, may help to improve clinical trial recruitment and retention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…The inclusion of patients should be encouraged through the development of inter-center networks and improvement of organizational phases. Investments in trial planning and facilities for patients enrolled in clinical trials can increase the number of patients in clinical trials [88][89][90].…”
Section: A Small Number Of Patients Benefit From Inclusion In Clinical Trialsmentioning
confidence: 99%
See 2 more Smart Citations
“…The inclusion of patients should be encouraged through the development of inter-center networks and improvement of organizational phases. Investments in trial planning and facilities for patients enrolled in clinical trials can increase the number of patients in clinical trials [88][89][90].…”
Section: A Small Number Of Patients Benefit From Inclusion In Clinical Trialsmentioning
confidence: 99%
“…The primary field of improvement is represented by organizational improvement and the need for investment in the research of active compounds, trial planning, and patients on trial tutelage [88][89][90].…”
Section: Improving Interventional Clinical Trials Design On Gbmmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous report showed a moderate correlation between the conduct of paediatric clinical trial activities and the burden of the disease (Bourgeois et al, 2014 ). Another study found that the access of a group of patients with cancer to clinical trials could be improved by reducing the financial burden, especially by taking into account travel costs in low‐income areas (Borno et al, 2018 ; Winkfield, 2020 ). Cameron et al considered using a quantitative patient burden assessment, the Patient Friction Factor (PFC), for clinical trials, to evaluate the feasibility of a clinical trial design (Cameron et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%